Attorneys and Accountants in a changung environment in South Africa: The case for multidisciplinary practice. - Cheze, M A C (Department of Public Law, 2024)
Thirty years ago, an individual faced with a particularly complex tax problem would have turned to his lawyer. Ten years ago, he would have turned to his accountant. Today, he may even turn to his bank manager~ In 1986, we see lawyers and accountants competing with the merchant banks, the trust companies, insurance companies and other financial institutions, not only in the tax areas but many others as well. These two disciplines, for so long accorded the dignity and status of professionals, today see their traditional domains being increasingly eroded. Accountants, themselves threatened by the financial institutions, are threatening the lawyers. The lawyers find themselves attacked on all fronts. Can these two professions continue to regard themselves as a "calling", or should they be adopting the stance of aggressive businessmen responding to negative environmental stimuli? In this report we highlight the threats facing the two professions: competition [primarily], inflation, technology, changing client attitudes and survival in a weakened South African economy. These threats, coupled to the extortionate cost of litigation and the "brain drain", are presented as arguments in favour of the professions being forced to consider what strategic response to adopt. We also examine the distinct threats faced by the professions due to their lack of marketing. Having interviewed various practitioners to obtain their viewpoints, we look at various strategic options open to the professions. The areas of synergy are critically appraised, and then we examine the theoretical as well as practical advantages and disadvantages of mergers and acquisitions. The theory applicable to mergers and acquisitions is shown to be particularly V ...... ,., apposite to the association of accountants and lawyers in a Multidisciplinary Practice. Various trends are also highlighted in the report. The most important of these is the phenomenal growth in size and scope of services of the accounting firms, and the trend worldwide towards closer association of the two professions. The threats outlined above are also presented as a trend. We show how the accountants have responded, to a limited extent, to market forces by setting up service companies, but the laW¥ers, even though under greater threat than the accountants, are shown to have been very slow in their response. In this respect the differing approaches to the needs of the marketplace by the two professions are highlighted. Having highlighted the areas of synergy, the strategic advantages and disadvantages of associating, and the viewpoints of the various practitioners, we conclude that the best response to the threats facing the two professions is to form a united front: a Multidisciplinary Practice. By Multidisciplinary Practice we mean the creation of a third entity, in the, form of a limited liability company, by a law firm and accounting firm. This multidisciplinary practice will thus consist·of practitioners of each discipline and will, through its linkage to the two firms, be accorded professional status. It will be bound by the Codes of Conduct of the professions. These Codes of Conduct however, are shown to have a distinct negative impact on the professions. They curtail the professions' activities in the marketplace, eg they are unable to advertise their services. We therefore conclude that these constraints have to be lifted to allow the vi multidisciplinary practice to compete on an equal footing with the financial institutions. The constraints are shown, in many respects, to be outmoded today. The underlying principles of the constraints are presented as being virtually identical in both professions, although lawyers are limited to a greater degree than accountants. In the final analysis then: the report highlights the historical trends of lawyers and accountants, and the inroads on their scope of services made by various institutions. Various strategic options are examined, and we conclude that the synergistic benefits and advantages to be gained by a Multidisciplinary Practice outweigh the problems and disadvantages of association. A Multidisciplinary Practice is thus presented as a viable and desirable entity in the South African marketplace.